The role of monetary policy in reducing inflation in Iraq through monetary sterilization mechanism. post-2003 - .k.beda, Sabreen; salih, Mohamed; abidalraheem, Thuria (Journal of Economics and Administrative Sciences, 2021)
The main objective of the central bank is to achieve price stability and target in fractionates. Therefore, the bank sought to use modern tools and policies in order to reduce the negative effects of the accumulation of foreign reserves represented by monetary sterilization, similar to developed and developing countries alike, but with different available tools that are possible and imposed by the local financial and monetary environments, such as the window for buying and selling foreign currency, open market operations and deposit facilities. And lending existing. Because any in crease in the monetary base resulting from the accumulation of foreign reserves will affect price stability directly due to the consumer nature of the Iraqi citizen. Despite the success of the monetary policy of targeting and reducing inflation rates and bringing it to zero degrees, the use of these tools and policy was at the expense of depleting a large part of foreign reserves in addition to the central bank in currying additional costs that weighed down its financial budget, in light of the large and steady increase in government spending. Consumer, external pressures and shocks in the Iraqi economy